Effectiveness of Malawian Law in Protecting Pangolins from Illegal Wildlife Trade - Jamzy Majamanda, James; Ndawazake Desire Zimba (Journal of Sustainable Natural Resources, 2025)
Illegal wildlife trade is one of the most common problems concerning wildlife conservation in Malawi. Pangolins are one of the most traded and trafficked animals despite laws being there to protect them from illegal wildlife trade. The study was conducted in February and March of 2023, to assess the effectiveness of the Malawian law in protecting pangolins from illegal wildlife trade, in the last three years (January 2020-January 2023, which is still on the rise. This study hypothesised that the present Malawian law does not effectively protect pangolins from illegal wildlife trade. A qualitative research with a social legal research approach was conducted, and data was collected through interviews and desk research. Primary data was collected through interviews using a questionnaire with judicial officers such as judges and magistrates and police officers in Mzuzu, Lilongwe, Zomba and Machinga, but also officers at the Department of National Parks and Wildlife including Lilongwe Wildlife Trust. Additionary questionnaires were administered to twenty (20) University of Malawi Law Students to understand their perception on pangolins and illegal wildlife trade in line with their legal stand. Secondary data was gathered by assessing Malawian law (The Constitution, National wildlife policy, National parks and wildlife Act and the Penal code)on how it is enforced and implemented and the challenges involved. Data was then analysed using the narrative analysis method. The study showed that illegal pangolin trade cases are still on the rise. The Malawian law has some strengths and weaknesses in dealing with illegal pangolin trade. There are several barriers to practical implementation of the law in Malawi. For instance, people are ignorant of the law in question, lack sensitisation, awareness and civic education, geographical set up of areas such as Mangochi and Machinga promote illegal pangolin trade, poor investigative and prosecution skills result into acquittals of some culprits, and that there is knowledge gap on the side of judicial officers in applying the law. It was therefore concluded that the law is not effective in protecting pangolins from illegal wildlife trade. Most importantly the provisions in the present law have to be maintained, but the enforcement and implementation of the law needs to be improved. People need to be civic educated to know how the law works.